Design and mixed integer linear programming optimization of a solar/battery based Conex for remote areas and various climate zones. (June 2021) - Taslimi, Melika; Ahmadi, Pouria; Ashjaee, Mehdi; Rosen, Marc A.
Highlights: Performing a transient simulation of a solar-based Conex for a remote area. Performance assessment of the proposed system for various cities in Iran. Mixed-integer optimization of a photovoltaic system based on hourly input data. Presenting a stand-alone photovoltaic system for practical purposes in Iran. Considering options available in the marketplace in Iran as decision variables. Abstract: In this research paper, a multi-objective optimization for sizing a stand-alone photovoltaic system for a Conex in remote areas is developed based on a mixed integer linear programming (MILP) technique. The stand-alone system is composed of a photovoltaic array, a cooling/heating system, battery banks, an inverter, and a charge controller. The MILP model is employed to obtain the optimal size and specifications of system components, including model and number of photovoltaic panels, the coefficient of performance of cooling/heating system, and the battery size, with respect to two conflicting objective functions, total cost and loss of power supply probability. The weighted factor method is employed in the model, and the final optimal solutions are achieved by MATLAB software. The suggested model is optimized for four cities in Iran, representing different climate types, but it can be utilized for any site with known climate data. In order to observe the conflict between the two objective functions, the Pareto frontiers are shown. The average cost of supplied electrical power is found to be 160, 000, 250, 000, 150, 000, and 60, 000 Iranian Rials per kWh, (180, 000 Iranian Rials is equal to 1 US dollar in April 2020), for Tehran, Tabriz, Kerman, and Bandar Abbas, respectively. Based on the optimization results, the system is cost-efficient and suitable for remote applications, especially in desert and semiarid regions. Hence, the proposed system can provide the required electricity of the Conex for approximate initial costs of 440 and 290 million Rials for Kerman and Bandar Abbas, respectively. Finally, the optimum solutions through various weighted factors are shown, considering operator purpose and budget preferences, which permit advantageous utilization of solar energy.